Relationship between well-being and social media usage among young adults in Malaysia - Labent, Shirly; Kong, Lek Chin; Wong Xin Lin, Jasmine; Chan, Siaw Leng (Global Academic Excellence, 2024)
Social media use has become prevalent swiftly, which has created several problems associated with well-being. The main purpose of this study was to examine the relationship between well-being and social media usage among Malaysian young adults. This study used a cross-sectional survey method. A total of 204 young Malaysian adults aged between 18 and 40 years old, 47.1% of males and 52.9% of females, participated in this study through purposive sampling. The demographic questions were used to obtain background data from the participants. The Psychological Well-being Scale (PWBS) was used to examine the overall well-being of Malaysian young adults, and the Social Media Engagement Questionnaire (SMEQ) was used to examine how often the participants use social media. Findings demonstrated that well-being and social media usage were positively correlated. Moreover, the findings also indicated a moderate level of well-being among Malaysian young adults. The findings of this study concluded that the strategic utilization of social media may benefit Malaysian young adults' well-being. Most Malaysian young adults have a moderate level of well-being, which could reflect their transitional nature of young adulthood due to navigating various life changes such as education, career choices, or relationships. This study establishes the framework for future research. It emphasizes the significance of young adults regulating their social media usage to protect their psychological well-being by fostering mindfulness in their social media activities. Implications and future recommendations are discussed in this study.